Challenges and potential of a collaborative approach to education reform - Bodilly, Susan J. (RAND, 2004)
Dissatisfied with the results of earlier efforts to improve educational outcomes in U.S. schools, the Ford Foundation developed a program called the Collaborating for Education Reform Initiative (CERI) that provided grants to collaboratives of community-based organizations in urban settings as a way to address systemic barriers to high-quality teaching and learning. Eight collaboratives signed on, and, over four years, the RAND Corporation assessed the progress of the program. The authors of this report found that the eight sites made varying degrees of progress and, while none had reached the final outcomes desired, some of the collaboratives offered considerable promise. Although success is far from certain, by adopting such techniques as clear communication of expectations, engaging school staff, and using data to alter strategies as necessary, collaboratives stand a better chance of becoming self-sustaining and positively affecting student learning.